PENGARUH VARIASI VARIABEL REAKSI PADA PROSES EKSTRAKSI REAKTIF MESOKARP SAWIT UNTUK MENGHASILKAN BIODIESEL - Pascalis Novalina; Arya Josua S; Taslim; Tjahjono Herawan (Jurnal Teknik Kimia USU, 2015)
The conventional method for the production of biodiesel needed the oil that is extracted from the biomass before it can be transesterified into fatty acid methyl esters (FAME). Reactive extraction can be used to produce biodiesel with high-yield, low production costs, reduce the reaction time and the use of reagents and co-solvents, making it easier to produce biodiesel. In this study, reactive extraction applied to produce biodiesel from palm fruit mesocarp extracted using dimethyl carbonate as a solvent and reagents, and novozym®435 as a catalyst. Methanol was replaced by dialkyl carbonates, particularly dimethyl carbonate. Dimethyl carbonate can be used as a solvent and as a reagent, so reactive extraction is very easy to apply. The parameters will be study are reaction temperature (50, 60, and 70 °C), reaction time (8, 16, 24 hours), the molar ratio of reactants (50: 1, 60: 1, 70: 1 n/n ), the concentration of novozym® 435 (5%, 10%, 15% wt).The results showed that the highest biodiesel yield can be achivied at conditions temperature of 60 °C, reaction time 24 hours, molar ratio of reactants palm mesocarp to DMC 1:60, and novozym®435 concentration of 10wt%. The results showed that the synthesis of biodiesel via reactive extraction using palm mesocarp as raw material requires a low production cost.